2011
DOI: 10.1016/j.envres.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor temperature is associated with serum HDL and LDL

Abstract: Background While exposures to high and low air temperatures are associated with cardiovascular mortality, the underlying mechanisms are poorly understood. The risk factors for cardiovascular disease include high levels of total cholesterol and low-density lipoprotein (LDL), and low levels of high-density lipoprotein (HDL). We investigated whether temperature was associated with changes in circulating lipid levels, and whether this might explain part of the association with increased cardiovascular events. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…Exposure to extreme temperatures can act as a trigger for CVD events due to changes in blood pressure, blood viscosity, blood cholesterol, and heart rate. 9,18,19 Cold weather is well known to be associated with a variety of autonomic responses in humans, including peripheral vasoconstriction, shivering, and increased blood pressure and heart rate. In patients suffering from ischemic heart disease, exposure to cold may cause a decrease in coronary blood flow, which could contribute to coronary spasm, chest pain, and even myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to extreme temperatures can act as a trigger for CVD events due to changes in blood pressure, blood viscosity, blood cholesterol, and heart rate. 9,18,19 Cold weather is well known to be associated with a variety of autonomic responses in humans, including peripheral vasoconstriction, shivering, and increased blood pressure and heart rate. In patients suffering from ischemic heart disease, exposure to cold may cause a decrease in coronary blood flow, which could contribute to coronary spasm, chest pain, and even myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Changes in cholesterol levels and the response of autonomic nervous system have been reported to increase CVD events during temperature extremes, which is a particular concern among older adults with limited cardiovascular reserve. [17][18][19] Previous studies have investigated the relative mortality risk of temperature on CVD. [20][21][22] However, this risk is heavily influenced by deaths among elderly persons.…”
mentioning
confidence: 99%
“…In particular, previous epidemiologic studies have investigated the relationship of single exposures with individual metabolic components rather than with the entire complex of metabolic alterations that constitute metabolic syndrome (11)(12)(13)(14)(15). Furthermore, previous studies have focused mainly on the associations between short-term temperature exposure and metabolic outcomes, which may reflect transient modifications not necessarily related to long-term risks (15,16).…”
mentioning
confidence: 99%
“…No changes were found in total cholesterol or triglycerides in relation to temperature increase. This study suggested that changes in HDL and LDL levels, which are associated with an increase in ambient temperature, may be among the underlying mechanisms of temperature-related cardiovascular mortality (Halonen et al, 2011). A study in Taiwan found that increased 1-year average ozone, PM and nitrogen dioxide were associated with elevated blood pressure, total cholesterol, fasting glucose, and HbA1c.…”
Section: Impact Of Climate Change and Air Pollution On Dyslipidemia Amentioning
confidence: 86%